CYSTINURIA: Crystals that Make a Baby Cry - Trivedi, Dhiraj J. (Indian J Clin Biochem, 2016)
Cystinuria is a common aminoaciduria due to a COAL transporter defect in renal tubular epithelium. Increased level of cystine in urine with occasional cystine crystal can be diagnostic. With reference to clinical examinations, symptoms and laboratory reports we present a case of primary cystinuria. Prevention of complication in cystinuric relies on detection at early stage and targeting treatment towards maintaining low level of urinary cystine level.